KEDUDUKAN PARA PIHAK DALAM PERJANJIAN KERJASAMA OPERASIONAL PENGEMBANGAN LAHAN PERUMAHAN DAN IMPLIKASINYA TERHADAPHAK PENGELOLAAN LAHAN - Sawitri, Galuh (Magister Kenotariatan Universitas Diponegoro, 2018)
AbstractÂ The unity of PT Pradipta Ratnapratala as the owner of the asset with PT Citra Mitra Properti (Ciputra Group) as investor in the Land Development Cooperation Agreement gave birth to a new business entity entity by the parties named